2022
DOI: 10.1038/s41598-022-21215-2
|View full text |Cite
|
Sign up to set email alerts
|

Predicting willingness to donate blood based on machine learning: two blood donor recruitments during COVID-19 outbreaks

Abstract: Machine learning methods are a novel way to predict and rank donors' willingness to donate blood and to achieve precision recruitment, which can improve the recruitment efficiency and meet the challenge of blood shortage. We collected information about experienced blood donors via short message service (SMS) recruitment and developed 7 machine learning-based recruitment models using PyCharm-Python Environment and 13 features which were described as a method for ranking and predicting donors’ intentions to dona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…Using the dataset from Yangzhou Blood Station in China, Wu et al 2022 gathered information about experienced blood donors recruited via short message service (SMS) and developed seven machine learning-based recruitment models [7]. Thirteen characteristics were outlined as a method for evaluating and predicting blood donors' intentions to donate.…”
Section: Application Of Machine Learning In Predicting Blood Donor Re...mentioning
confidence: 99%
“…Using the dataset from Yangzhou Blood Station in China, Wu et al 2022 gathered information about experienced blood donors recruited via short message service (SMS) and developed seven machine learning-based recruitment models [7]. Thirteen characteristics were outlined as a method for evaluating and predicting blood donors' intentions to donate.…”
Section: Application Of Machine Learning In Predicting Blood Donor Re...mentioning
confidence: 99%
“…78,79 There are increasing number of publications reporting advanced techniques to predict transfusion needs in patients. [80][81][82][83][84] Recent studies have shown the potential for data on transfusion usage to forecast the demand for both red blood cell [85][86][87] and platelet transfusion requirement. [88][89][90][91] How widely and rapidly these findings can be rolled out in hospital information systems remains to be seen.…”
Section: The Value Of Hospital Datasets and Data Repositories To Expl...mentioning
confidence: 99%
“…Directly embedding learning systems within EHRs has huge potential but their implementation remains a significant challenge 78,79 . There are increasing number of publications reporting advanced techniques to predict transfusion needs in patients 80–84 . Recent studies have shown the potential for data on transfusion usage to forecast the demand for both red blood cell 85–87 and platelet transfusion requirement 88–91 .…”
Section: The Value Of Hospital Datasets and Data Repositories To Expl...mentioning
confidence: 99%
“…They found that self-efficacy and approval from others, underpinned by coping appraisals and organizational trust, play a critical role in the intention to donate [20]. A study in Jiangsu, China, used machine learning methods to predict blood donation intentions and to improve the recruitment rate of blood donors [21].…”
Section: Introductionmentioning
confidence: 99%